Perancangan Sistem Reservasi Meja dan Makanan Pada Rumah Makan Berbasis Web (Studi Kasus Di Rumah Makan Ayam Bakar Celup Mang Rojak) - Meiniarti Meiniarti; Rahmat Gunawan; Yahya Suherman; Anjar Setiawan (Infotek: Jurnal Informatika dan Teknologi, 2022)
This study aims to design a reservation system table and food at Roast Chicken Restaurant Mang Rojak that has not utilized internet technology. This application is a solution to the reservation problems that occur and can be used as a means of developing services to customers. The system development method used is the waterfall model. This method consists of several stages of activity flow that runs in one direction from the beginning to the end of the system development project, starting from the analysis of design, design, coding, testing and system implementation. In the analysis phase, the data were collected by observation and interview. The testing of this application is done with Black Box Testing. The results of the study have provided sufficient information about the current food ordering procedure, so that the new system is needed. This table and food reservation information system is website-based that supports online ordering process. This system also provides menu price information and other promotions without coming to the restaurant. Development of this application is needed in order to be able to help issues related to information needs both for the company and customers